High Efficiency CMOS Class E Power Amplifier Using 0.13 μm Technology-0 - Murad, S.A.Z.; Ahamd, M.F; M. Mohamad, Shahimin; Ismail, R.C; Cheng, K.L; Rohana, Sapawi (IEEE, 2012)
This paper presents the design of a 2.4-GHz CMOS Class E power amplifier (PA) for wireless applications in Silterra 0.13-μm CMOS technology. The Class E PA proposed in this paper is a single-stage PA in a cascode topology in order to minimize the device stress problem. All transistors are arranged in parallel to decrease on-resistance for high efficiency with on-chip input and output impedance matching. The simulation results indicate that the PA delivers 11.9 dBm output power and 53% power added efficiency (PAE) with 1.3-V power supply into a 50-Ω load. The chip layout is 0.27 mm2.